Recent advances in Representational structures and pharmacological activities of Polygonatum odoratum polysaccharide - Li, Cong; Cai, Renyue; Luo, Canpeng; Li, Jiahui; Wu, Zuoduo; Dong, Jiuming (International Journal of Natural Resources and Environmental Studies, 2023)
With the growing market of Chinese medicinal materials in China, Polygonatum odoratum is popular among the public as the leading medicinal materials in Hunan Province, and Polygonatum odoratum is recognized as the first batch of Chinese medicinal materials with the same origin as food and medicine by the National Health Organization. As one of the main active ingredients, its polysaccharide has anti-aging, anti-oxidation, immune regulation, hypoglycemia and other effects. In this paper, Extraction and purification methods, structure elucidation and characteristics, biological activity and mechanism, innovative application, biosynthesis mechanism research and development prospect of this herb were reviewed.